The Safety of Influenza and Pertussis Vaccination in Pregnancy in a Cohort of Australian Mother-Infant Pairs, 2012–2015: The FluMum Study. (23rd November 2018) - McHugh, Lisa; Marshall, Helen S; Perrett, Kirsten P; Nolan, Terry; Wood, Nicholas; Lambert, Stephen B; Richmond, Peter; Ware, Robert S; Binks, Paula; Binks, Michael J; Andrews, Ross M
Abstract: Background: Inactivated influenza vaccine (IIV) and pertussis vaccination are recommended in pregnancy. Limited safety data exist for women who received IIV vaccine during the first trimester of pregnancy or received both vaccines in pregnancy. We assessed adverse birth outcomes between vaccinated and unvaccinated pregnancies. Methods: Among prospectively enrolled Australian "FluMum " participants (2012–2015), primary exposure was receipt and timing of IIV during pregnancy. Primary outcomes included preterm birth, low birthweight at term (LBWT), and small for gestational age (SGA). We compared birth outcomes for IIV in pregnancy with women unvaccinated in pregnancy using Cox proportional hazard ratios (HRs) with 95% confidence intervals (CIs). Adjusted HRs (aHRs) controlled for potential confounding variables. Sensitivity analyses were conducted in a subgroup of women who received pertussis vaccination during pregnancy to assess whether associations between IIV and adverse outcomes were maintained after adjusting for pertussis vaccination. Results: Among 8827 participants in our study, women who received IIV in pregnancy did not have an elevated risk of an adverse birth outcome compared with unvaccinated pregnant women: preterm births (HR, 1.10 [95% CI, .92–1.31]; P = .28); LBWT (HR, 1.05 [95% CI, .76–1.44]; P = .77); or SGA (HR, 0.99 [95% CI, .86–1.15]; P = .94). Adjustment for pertussis vaccination during pregnancy yielded similar results: preterm births (aHR, 1.05 [95% CI, .82–1.34]; P = .69); LBWT (aHR, 0.81 [95% CI, .50–1.29]; P = .37); SGA (aHR, 0.92 [95% CI, .74–1.14]; P = .43). There was no evidence of elevated risk by trimester of IIV. Conclusions: No significant associations were found between maternal IIV or pertussis vaccination in pregnancy and adverse birth outcomes, regardless of the trimester of pregnancy a vaccination was given compared to unvaccinated pregnancies. Abstract : We found no evidence of adverse birth outcomes (prematurity, low birthweight at term, or small for gestational age) following influenza vaccination in pregnancy nor of increased risk associated with the trimester of vaccination, or when combined with pertussis vaccination in pregnancy.